Ultra-endurance race performance and muscle mass as predictors of cognitive capacity - Vilite, Deina; Lismane, Diana; Raudeniece, Jelena; Laizane, Linda; Gersone, Gita; Barone, Ilze; Justamente, Ilze; Kovtuna, Kristiana; Roelands, Bart; Zolovs, Maksims; Reihmane, Dace (Frontiers in Cognition, 2025)
IntroductionThis study investigated which objective measures best predict cognitive performance in ultra-endurance athletes.MethodsForty-three recreational cyclists completed a race of ?341 km over 18 h, with cognitive function assessed using a three-stage Stroop Test before, immediately after, and 24 h post-race. For each stage, results from the three time points were combined and analyzed using regression analyses to examine their relationship with various anthropometric, metabolic, and performance-related parameters.ResultsHigher average race speed was associated with improved simple reaction time, while longer race duration predicted better performance in more cognitively demanding tasks, such as inhibitory control. Muscle mass was the only anthropometric variable significantly linked to enhanced cognition. Other factors-including age, percentage of heart rate reserve, training volume, fat mass, lean mass, bone mass, and metabolic markers-showed no associations.ConclusionThese findings suggest that race pacing and muscle mass play key roles in supporting cognitive resilience during prolonged physical exertion.